National park behavioural intention among international tourists: the combined effect of national park attractiveness, green practices, sustainability, subjective norm, perceived behavioural control, satisfaction and mobile applications / Payam Mihanyar - Payam, Mihanyar (2016)
Studies on destination attractiveness as the main driver to behavioural intention have been the mainstay in tourism literature. Of late, attitudes towards sustainability and green practices have emerged as critical areas in tourism development and growth. Tourists, especially those from developed countries have voiced their strong concern over environmental degradation and this has led to conservation efforts in a number of developing countries' national parks. As such Malaysian National Parks (MNP) strive in attracting tourists from developed countries to generate more yields, which leads to natural area protection. This thesis extended the behavioural intention literature by incorporating mobile apps as another driver to behavioural intention, as tourists embrace technology, love to get connected and seek greater involvement in their tourism experience. In addition, tourism experience has been undergoing changes due to today's mobile apps expansion, as it offer numerous means by which tourist constructs the tourism experience by learning, understanding, self-actualizing, and feeling the places visited and the cultures embedded in these places. In this regard, the combined effect of national park attractiveness (NPA), national park green practices (NPGP), national park sustainability (NPSus), national park subjective norm (NPSN), national park perceived behavioural control (NPPBC), national park mobile apps (NPMA), and national park satisfaction (NPSat) on tourists behavioural intention visiting MNP as a robust model named National Park Behavioural Intention (NPBI) remains unknown despite increasing importance of aforementioned variables in tourism industry. In an effort to understand the effect of study constructs in the NPBI Model, this study first established the dimensions and items of the constructs. Secondly, the researcher empirically investigated the effect of the constructs. Additionally, the mediation effect of NPSat in the NPBI Model, whether partial or complete, was also examined. The three critical constructs influencing NPBI are NPGP, NPSus, and NPMA. Theoretically, this study adds value to theory of planned behaviour (TPB) by confirming the influence of aforementioned variables in the NPBI Model. In addition, in terms of items and dimensions of NPA, this study expands the Gearing, Swart, Var (GSV) Model. Practically, this study provides practical implications for the public and private sectors in effective planning, development, and marketing of national parks.